Swarm intelligence for resource management in internet of things - Hassanien, Aboul Ella; Darwish, Ashraf (Intelligent data centric systems., 2020)
This book guides you through Internet of Things (IoT). IoT represents a new revolution of the Internet network which is driven by the recent advances of technologies such as sensor networks (wearable and implantable), mobile devices, networking, and cloud computing technologies. --